Standard Time Measurement and Optimization of the Number of Labor at Ruang Klambi Convection with the Approach of Work Sampling and Work Load Analysis (WLA) - Khairunnissa, Lydwiza Firdananda Khairunnissa; Nurhasanah, Nunung Nurhasanah; Purwandari, Aprilia Tri Purwandari; Khairunnissa, Lydwiza Firdananda (JURNAL TEKNIK INDUSTRI, 2025)
Several companies indirectly give excessive workloads that are considered to increase productivity. Besides workload, the work environment is important in encouraging employees to work optimally. Ruang Klambi Convection does not have a good work system due to the absence of an effective work schedule and poor work environment conditions. This can allow for overload or excessive workload on each worker. The primary motivation for this study is to improve work efficiency at Ruang Klambi Convection, which faces problems of excessive workload and a non-optimal work environment. Through the Work Sampling and Work Load Analysis approach, this study aims to measure standard production time and determine the optimal number of workers, thus reflecting a significant paradigm in measuring standard time. This study was conducted by calculating the standard time required to produce a midi dress with an average order of 30 pieces, measuring and analyzing the workload level from each workstation, and determining the optimal number of workers. Based on the calculations, the results show that the standard time to fulfill an order of 30 pieces is 106.2 hours (equivalent to 5 days). In addition, based on the analysis of the workload of each workstation, two workstations are classified as overloaded, namely workstations I (Pattern Making and Cutting) and II (Sewing), so it is necessary to add a worker to both workstations to achieve a fit workload.